Prevalence of Malocclusion and Its Relationship with Deleterious Oral Habits Among 18-25 Years Old Adults Attending A Private Dental College- A Hospital Based Cross Sectional Study - GANAPATHI, AMANTHI; PRABAKAR, JAYASHRI; JEEVITHA, M. (The journal of contemporary issues in business and government, 2021)
Abnormal oral habit could alter a normal growth of oro-facial structure and alo related to malocclusion which is caused by various reasons such as unusual repetitive behaviours in oral cavity To evaluate the prevalence of malocclusion and its association with deleterious oral habits in adults from 18-25 years old. The present cross-sectional study was undertaken to evaluate the prevalence of malocclusion and its association with deleterious oral habits in adults, from 18- 25years old in south Indian population. Case sheets of 158 patients were evaluated for adverse oral habits and malocclusion. The collected information from the case sheet of the patients was entered in Microsoft Excel 2012.Descriptive statistics were expressed by means of frequency and percentage and Chi-square test was used to find the association between Independent variables (Age and Gender) and Deleterious Oral Habits. Level of statistical significance was set at p<0.05. Total sample size n=158,out of which patients with biting habits-52.91%,Tongue thrusting- 25.58%,Mouth breathing-15.82%,Lip biting-8.86%,Thumb sucking-6.33%,biting and lip biting- 3.80%,Tongue thrusting and lip biting-3.80%,Thumb sucking biting, Thumb sucking and mouth breathing-0.63%. In conclusion, the majority of the study population had a biting habit and Angle’s class I malocclusion and also found that there was no relationship between Malocclusion and deleterious oral habits among the study subjects enrolled in the present study.